The Documentary distribution toolkit how to get out, get seen, and get an audience - Gordon, Rachel (Abingdon, Oxon Routledge, 2022)
"Mapping out a diverse journey through documentary distribution, this book is a comprehensive global how-to reference guide providing insights into the landscape of documentary distribution; targeting the right audiences to expand the reach of your documentary; and building a sustainable career. Detailing how to prepare your documentary, strategies for crowdfunding, working with documentary organizations and online platforms, and outlining the channels to consider, The Documentary Distribution Toolkit demystifies the process of distributing your documentary. Featuring case studies and interviews including filmmaker Alice Elliot, representatives from public television stations such as ARTE, ZDF, Al Jazeera, TRT (Turkey), NHK, as well as drawing on author Rachel Gordon's over 20 years of experience working in documentary distribution. Foregrounding documentaries for non-profit and educational purposes, each chapter gives guidance on how to think locally and globally, on money matters to consider, and personal questions to answer before proceeding to help filmmakers manage their time, money, and energy wisely. This book empowers the filmmaker to distribute their documentary in an effective and strategic manner. Providing concrete advice on how to navigate the documentary ecosystem beyond the classroom, this is the ideal book for professional and emerging documentary filmmakers, as well as students who are looking to distribute their documentary films"-- Provided by publisher.
Prepare yourself : think before you shoot -- The hard work of crowdfunding -- Documentary organizations worth your time and money -- Now available online--how to stream -- Creating community--partnerships with purpose -- Facilities and academic professional development -- Public broadcasters and the specialty TV ecosystem.
Includes glossary and index .
Keywords: Documentary films -- Distribution; Documentary films -- Production and direction